HUBUNGAN KECEMASAN DENGAN PEMILIHAN ALAT KONTRASEPSI DALAM RAHIM (AKDR) PADA AKSEPTOR KB SUNTIK DI PRAKTIK MANDIRI BIDAN SULISWINARSIH, SST KABUPATEN PROBOLINGGO 2019 (Relationship Between Anxiety With Selection Of Contraception Equipment in Rahim (IUD)) - Azizah, Fifin Maulidatul; Nanda, Diah Mega (STIKes Maharani Malang, 2020)
Introduction:Indonesia currently occupies the fourth position with the largest population of 258,704,986 people, and in 2016 the maternal mortality rate in East Java reached 91 / 100,000 live births. Anxiety is a natural disorder that is characterized by feelings of fear or anxiety that are deep and ongoing. Anxiety tends to produce confusion and distortion of perception. Situations like this can prevent a person from choosing the right contraception for him. Inappropriate choice of contraception will result in maternal death from 4T (too young, too often and too close, too old). The purpose of this study was to analyze the relationship of anxiety with the choice of IUD contraception in injecting family planning acceptors. Method:This study used a correlation analysis design with a cross sectional approach, where data were obtained from questionnaires using HRS-A measuring instruments obtained from injecting KB acceptors in the Independent Practice of Midwife Suliswinarsih,SST Probolinggo Regency 2019 conducted on April 9 to 20 May 2018 with a population of 30 KB acceptors with total sampling technique. Data collection includes editing, tabulating, coding, entering, and cleaning then the data are analyzed using SPSS with chi square test analysis with p-value = 0.05. Results and Analysis : The results showed cases of anxiety experienced by injecting family planning acceptors in the IUD selection of anxiety levels were 9 respondents heavy and 9 respondents were heavy or 30% each. Most respondents who chose other contraceptives amounted to 83.3% or as many as 25 respondents. P-value = 0,000. Conclusion of the study, there is a relationship between anxiety with the selection of contraceptives in the womb at the injection KB acceptor. Discussion: The recommended advice is that health workers in the Independent Practice of Midwife Suliswinarsih,SST Probolinggo RegencyÂ improve more about contraceptive services, especially the IUD, especially about handling side effects in the use of the IUD.